The multi-level context for local climate governance in Germany: The role of the federal states - Peter Eckersley; Kristine Kern; Wolfgang Haupt; Hannah Müller (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2021)
This report is a product of the ExTrass project, which is funded by the German Federal Ministry of Education and Research to help medium-sized and large cities in Germany to prepare for the increased frequency of extreme weather events, particularly heavy rainfall and heatwaves. The project examines the drivers and barriers for urban climate adaptation and mitigation, with a particular focus on three case study cities: Potsdam, Remscheid and Würzburg. Amongst other things, the project team evaluates the efficacy of urban greening initiatives, works towards climate-sensitive urban planning, contributes data on city climate, educates the population on risks and improves contingency plans. It also provides a platform for knowledge exchange to help cities learn from each other. Cities are responsible for about 70% of global greenhouse gas emissions and are also particularly vulnerable to the impacts of climate change. Extreme weather events can result in significant damage to property and pose major risks to urban populations. Yet, municipalities are not able to manage these risks alone: in order to understand how they are seeking to combat change we need to examine the contexts within which they operate and their relationships with other key actors. This report focuses on the multi-level nature of the German state, with a particular focus on the role of the Bundesländer regional governments. It shows how the climate and energy priorities of individual states are largely shaped by their political and economic interests, and result in them adopting different approaches to working with municipalities. It shows that although Germany relies overwhelmingly on interdependent, vertical relationships between tiers of government to coordinate and implement climate policy, states that do not have a historical reliance on fossil fuel resources, and/or in which the Green Party form part of the governing coalition, have provided more resources and support to municipal governments to act on the issue.
Keywords: 710; Klimapolitik; Teilstaat; Kommunaler Finanzausgleich; Deutschland